Neuropharmacological Activity of the Acetonic Extract of Malpighia mexicana A. Juss. and Its Phytochemical Profile - Dante Avilés-Montes; David Osvaldo Salinas-Sánchez; César Sotelo-Leyva; Alejandro Zamilpa; Franceli Itzel Batalla-Martinez; Rodolfo Abarca-Vargas; Juan Manuel Rivas-González; Óscar Dorado; Rodolfo Figueroa-Brito; Vera L. Petricevich; Dulce Lourdes Morales-Ferra; Manasés González-Cortazar (MDPI AG, 2023)
Mental and neurological disorders are conditions that affect thoughts, emotions, behavior, and relationships. Malpighia mexicana A. Juss. is a plant used in Mexican traditional medicine for the treatment of such disorders. This work aimed to investigate the antidepressant, anxiolytic, sedative, hypnotic, and anticonvulsant effects of the acetonic extract (MmAE) of M. mexicana and its fractions (F3, F4-10, F14) using the forced swimming test (FST), elevated plus maze (EPM), open field test (OFT), pentobarbital-induced sleep test (PBTt), and pentylenetetrazol-induced seizure test (PTZt). MmAE, F3, F4-10, F14, and vehicle were administrated orally 24, 18, and 1 h prior to the evaluations. Imipramine (15 mg/kg, p.o.) was administrated 1 h prior to the evaluations as a positive control for the FST, while diazepam (1 mg/kg, p.o.) was administrated 1 h prior to the evaluations as a positive control for the EPM, OFT, PBTt, and PTZt. MmAE had an anxiolytic effect; MmAE and F3, F4-10, and F14 showed an antidepressant effect, sedative effect, hypnotic effect, and anticonvulsant effect. Using HPLC, we identified the compounds quercetin 3-O-rutinoside (1), kaempferol 3-O-glucoside (2), luteolin 7-O-glucoside (3), quercetin (4), and kaempferol (5) in MmAE and compounds (1), (2), and (3) in F14. Using GC-MS, we identified α-tocopherol, phytol, and β-amyrin in F3; β-tocopherol, phytol, β-sitosterol, and β-amyrin in F4-10; and α- tocopherol, phytol, β-sitosterol, and β-amyrin in F4-10. The neuropharmacological effects found in this work may be due to the presence of vitamins, phytosterols, terpenes, and flavonoids. This research requires further study to clarify the mechanisms of action of the identified compounds.